UML2 activity diagram based programming of wireless sensor networks - Fuchs, Gerhard; German, Reinhard (Proc. of the 2010 ICSE Workshop on Software Engineering for Sensor Network Applications, 2010)
Wireless Sensor Networks (WSNs) consist of sensor nodes (spots). In the frame of our ongoing ACOOWEE project we assay how spots can be programmed so that they collaborate and fulfil a common task. The novelty of our work is that we see activities as scripts that can be executed by spots. Programming means to compose activity calls like bricks by specifying their sequence (workflow description) and the executing spot (action allocation). We are developing a framework for Sun SPOTs. We use and adapt the expressiveness of UML2 Activity Diagrams (UADs) and program UADs with Papyrus UML. Our interpreter executes them after a transformation. A successful example experiment with 6 Sun SPOTs indicates us that the idea of the ACOOWEE-project could become interesting for programming distributed operation, concurrency, synchronization and data aggregation of WSNs. Currently we are extending our framework and increasing our network. To draw conclusions for WSNs in general, further research is necessary. © 2010 ACM.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.IMMD7.uml2ac
Keywords: ACOOWEE; activity oriented programming; wireless sensor networks